2021
DOI: 10.3389/fpsyg.2021.759685
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Involuntary Mental Imagery in an Ecologically-Valid Task

Abstract: Laboratory tasks (e.g., the flanker task) reveal that incidental stimuli (e.g., distractors) can reliably trigger involuntary conscious imagery. Can such involuntary effects, involving competing representations, arise during dual-task conditions? Another concern about these laboratory tasks is whether such effects arise in highly ecologically-valid conditions. For example, do these effects arise from tasks involving dynamic stimuli (e.g., simulations of semi-automated driving experiences)? The data from our ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Future research could also focus on different working memory processes related to mental representation manipulations in other sensory modalities (e.g., one cannot rotate auditory content, so mental rotation performance does not necessarily represent ability to manipulate verbal mental representations, which should be related to auditory hallucinations) and their relationship with schizotypal personality traits and clinical populations. As an example, the ability to inhibit involuntary verbal imagery (e.g., Velasquez, Gazzaley, Toyoda, Ziegler & Morsella, 2021) could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could also focus on different working memory processes related to mental representation manipulations in other sensory modalities (e.g., one cannot rotate auditory content, so mental rotation performance does not necessarily represent ability to manipulate verbal mental representations, which should be related to auditory hallucinations) and their relationship with schizotypal personality traits and clinical populations. As an example, the ability to inhibit involuntary verbal imagery (e.g., Velasquez, Gazzaley, Toyoda, Ziegler & Morsella, 2021) could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Walker (2019) found substantive rates of insuppressible subvocalizations (~50% of the 30 trials) even when the stimulus was presented briefly (< 200 ms) or when the stimulus was presented under conditions of perceptual load (the stimulus was encircled by six other line drawings). In another experiment ( Velasquez et al, 2021 ), stimulus-elicited insuppressible imagery was observed even when the visual, eliciting stimuli were presented within a complex, dynamic scene (a movie) and the participant was engaged in secondary tasks that are known to induce cognitive load.…”
Section: Introductionmentioning
confidence: 99%